Characterization of chalcone isomerase 4A \((CHI4A)\) gene in \(Pueraria mirifica\) - Thu Thuy, Cao Thi; Bich Ngoc, Nguyen Thi; Kieu Oanh, Pham Thi; Thu Dung, Cao Thi; Thu Hue, Huynh Thi (Academia Journal of Biology, 2023)
Pueraria mirifica is a popular medicinal plant and is rich in phytoestrogens, especially isoflavonoids. The chalcone isomerase (CHI) gene is well-known as a key factor in biosynthetic pathways such as flavonoid, isoflavonoid, and anthocyanin biosynthesis. Among four CHI subfamilies, group IV remained largely uncharacterized in P. mirifica. By isolation and gene cloning, the CHI4A gene was amplified and sequenced. A dataset that included CHI4A genes from isolation, transcriptome, and Glycine max CHI4A was constructed for analysis. A total of 31 single nucleotide polymorphism (SNPs) was detected among sequences and 14 SNPs were found in P. mirifica subgroups. Thirteen SNPs changed the amino acid sequences of CHI4A genes; however, they do not affect core active residues in the protein structure. Two active sites typical for group 4 CHI in the Fabaceae family: Ile50 and Tyr106; and one conserved site Asn113, were found in this study, which is similar to the result of the previous study on CHI4. A three-dimensional protein model of isolated P. mirifica CHI4A enzyme was constructed with a high confidence level. The result provides more information about the variation and protein profile of the CHI4A gene for further experiments.